FESTIVAL PUISI RAKYAT NUSANTARA SEBAGAI SALAH SATU MODIFIKASI MODEL PEMBELAJARAN JOYFULL LEARNING DALAM PEMBELAJARAN TEKS PUISI - Kusuma, Emy Rizta (University of Brawijaya, 2021)
AbstractThe learning model of the Festival Puisi Rakyat Nusantara is one of the active and creative literature learning model. This model is also supported by constructivism learning theory which teaches student to construct their own experiences and understandings independently. In addition, Festival Puisi Rakyat Nusantara is a development of the Joyful Learning model. This aims to create a relax and fun learning atmosphere in studying poetry texts. This model is designed to overcome problems in learning literature, especially in poetry. By this model, students are more creative in understanding the learning of poetry texts. In addition, students are also trained to be confident in expressing their opinions when interpreting the contents of the poetry text that have been learned.